Fault-Plane Markings as Displacement Sense Indicators - Tjia Hong Djin (Geological Agency, 2014)
DOI:10.17014/ijog.v1i3.177In order to determine the sense of fault motion, older textbooks advise to stroke the fault surface parallel to its striations, or slickensides. The smoother touch is felt when one’s palm moved in the direction of the adjacent fault surface. Laboratory triaxial tests and abundant field evidence proved this ‘smoothness criterion’ of producing ambiguous results. The first published field evidence contradicting the criterion probably originated from the Lokulo area in Central Jawa over half a century ago. Similar findings from elsewhere around the world have also been printed. A practical nomenclature has since developed. The types of reliable fault-plane markings in various rock types are now known. Recognition of fault-movement sense is essential when outcrop size is limited such as in underground exploration and in trenches. In addition, the present article also shows examples how the sense of faulting is applied to arrive at determining structural evolution of a rock body. The method is readily applied to solve structural problems of more extensive geological terranes.